How Do You Comprehend Tahilalats Comic? - Jayaputri, Herlandri Eka (Master Program in Linguistics, Diponegoro University, 2017)
This study discusses the use of the cooperative principles and the conversational implicatures in Nurfadli Mursyid’s Tahilalats comic. Tahilalats is one comedy comic in Line Webtoon. The comic contains four panels in each episode, and its stories concern social phenomena. However, the readers said that Tahilalats comic was difficult to understand. This was the reason the writer conducted this study, which was an analysis of the use of the cooperative principle in Tahilalats comic. The study aimed at finding the forms of conversational implicature and describing the functions of conversational implicature in the comic. This study was focused on 30 episodes of the comic, and to collect the data the writer used simak and catat techniques (Sudaryanto, 1993). The results are related to the cooperative principle and the conversational implicature. The violation or compliance of the cooperative principles can describe the implicatures in the conversation. The uses of both produce humorous effects because these potentially lead the reader to misunderstand the comic when reading explicitly. However, reading the comic further, the reader will understand the implicit meanings.